Net Application On Contact Management System - Dr Govinda Rajulu.G, Dr Vijayakumar.M.V, Dr Kalvikkarasi.S (International Journal of Advanced Science and Technology, 2020)
The ultimate objective of the contact management system is to improve customer communication and secure relevant data and activity of customer. Even reduces manual work for managing details through internet. This system not only capable of storing the details about the pre-existing customer but also performing necessary updates, as well as adding new information about recent customer activities. Keep track of phone calls, emails, and every type of communication in one consolidated online database, which can be updated even on mobile devices like tablets and smartphones.